Social Exclusion and Austerity Policies in England: The Role of Sports in a New Area of Social Polarisation and Inequality? - Collins, Mike (2015)
Poverty still counts as the core of social exclusion from sport and many other domains of people’s lives. In the first part of this paper, we shortly describe the recent poverty trends in England, and identify groups that are more at-risk of being poor and socially excluded. We then focus on the relationship between poverty, social exclusion and leisure/sports participation, and describe a case study that addresses young people’s social exclusion through the use of sports (i.e., Positive Futures). Although further analysis is warranted, it would seem that growing structural inequalities (including sport participation)—with their concomitant effects on health and quality of life—are further widened and deepened by the policy measures taken by the Conservative-Liberal Democrat coalition in the UK. In addition, within a climate of austerity, sport-based social inclusion schemes are likely to become wholly inadequate in the face of exclusionary forces such schemes envision to combat.